Electromagnetic Field (EMF) Profile and Baselines at a Non- Haunted Control Location - Schumacher, David; Biddle, Kenny; Vickers, Tim (Journal of Scientific Exploration, 2023)
There has been little to no environmental and experience data collected at randomly selected non-haunted control sites despite the call for researchers and field investigators to do so over twenty years ago. Electromagnetic Fields (EMFs) and their association and correlation with haunted locations and haunt-type phenomena have been studied by both academics and hobbyist ghost hunters/paranormal investigators. The field has progressed over the years with mixed results and some within site controls. However, there is still a lack of data collected at non-haunted control locations, and many questions remain on how to collect and analyze baseline data. The current study was conducted to collect multi-hour multiple-run baseline EMF data to explore EMF profiles and to better understand how EMF readings can vary temporally across a 3-axis EMF meter at a non-haunted control site. Results showed that a non-haunted control site had complex time-varying magnetic fields during long-term data collection periods at various days and times, similar to locations deemed to be anomalous. Limitations of the study are noted, and future research is suggested.